2018
DOI: 10.3892/or.2018.6526
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Kank1 gene inhibits human lung cancer progression in�vitro and in�vivo

Abstract: Kank1, an important member of the Kank gene family, plays an important role in the development of many malignant tumors. As a brand new tumor-suppressor gene, the expression of Kank1 gene has been revealed to be downregulated or absent in many malignant tumors. However, there is no study concerning the specific role of Kank1 in the development and progression of lung cancer. In the present study, we found that the Kankl gene was significantly downregulated in human lung cancer and lung cancer cells. When the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…A series of studies had shown that KANK1 exerted an anti-cancer role in various tumors. For instance, increased KANK1 expression curbed the progression of gastric cancer [23] and lung cancer [28]. Moreover, KANK1 enhancement repressed cell cycle and accelerated cell apoptosis in brain glioma [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies had shown that KANK1 exerted an anti-cancer role in various tumors. For instance, increased KANK1 expression curbed the progression of gastric cancer [23] and lung cancer [28]. Moreover, KANK1 enhancement repressed cell cycle and accelerated cell apoptosis in brain glioma [49].…”
Section: Discussionmentioning
confidence: 99%
“…Also, KANK1 depletion promoted the amplification of the centrosomal [27]. Moreover, it was proved as a suppressor in various tumors [28][29][30]. For instance, KANK1 impeded the progression of human malignant peripheral nerve sheath tumors via promoting cell apoptosis [29].…”
mentioning
confidence: 99%
“…However, translocation of Bax and Bcl-2 may lead to changes in mitochondrial membrane proteins resulting in the release of cytochrome C, activating the Caspase family and eventually leading to apoptosis [36,37]. Recently, it has been reported that the up-regulation of the KANK1 gene can inhibit the development of lung cancer both in vivo and in vitro, and its mechanism is closely related to cell apoptosis and tumour invasion and metastasis [38].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the protein levels of CXXC5, KANK1, EMT proteins (Vimentin and E-cadherin) and signaling proteins (β-catenin and Axin2), Western blotting was conducted followed the description of a previous study. 34 It is worth mentioning that the compositions of cell lysis buffer we used in the present study were radioimmunoprecipitation assay buffer (Thermo Fisher Scientific, Waltham, USA) and 1% phenylmethanesulfonyl fluoride (Seebio, Shanghai, China). Besides, the primary antibodies included anti-GAPDH (normalization protein), anti-CXXC5, anti-KANK1, anti-Vimentin, anti-E-cadherin, anti-β-catenin and anti-Axin2 (Cell Signaling Technology, Danvers, USA) with a dilution of 1:500.…”
Section: Western Blottingmentioning
confidence: 99%